How dare the sun rise : memoirs of a war child - Uwiringiyimana, Sandra; Pesta, Abigail (Katherine Tegen Books, an imprint of HarperCollins Publishers, 2017)
The author shares the story of her survival of the Gatumba massacre, despite losing her sister, and how after moving to America she found healing through art and activism.